Requirements elicitation and analysis: towards the automation of software project risk management - Nordin, Azlin; Abdullah, Lili Marziana; Mohamad Fadzil, Farihin Diayana; Roselan, Nor Aqila Syamira (2014)
Risk management (RM) has always been the focus of software project management studies. The abilities to monitor and control the software project risks are among the critical issues examined by various researchers. This paper discusses steps in the RM process based on Boehm model. A survey was conducted to know the perceptions of respondents on their practices of managing project risks. This paper also reports the results of the survey concerning the desired features for risk management tool (RMT). In addition, a comparison with other RM process model is also included. Requirements were gathered from domain experts and were analyzed. Based on the results, the authors proposed, designed and developed the tool to automate the Boehm’s RM process.